Effects of supplemental microbial phytase on performance of broiler chickens - Koskinen, Tuomo; Piironen, Jari; Hakonen, Tiina (Agricultural and Food Science, 1994)
Three trials were conducted on a total of 5100 broiler chicks (0-5.5 weeks) to study the effects of different microbial phytase (Aspergillus niger) supplementations (250-1000 phytase units = PU/g) on the performance and bone mineralization of birds and on the utilization of phosphorus compared with the effects of mineral P additions as dicalcium phosphate. The basal diets (negative controls) were principally composed of soya bean meal (SBM) and grain (wheat, barley, oats) supplemented with up to 0.10% mineral P; the positive control diets were supplemented with 0.24-0.30% mineral P. Compared with the negative control groups, which were fed diets with 0.05% mineral P either during the whole rearing period or during the starting period only, phytase addition increased live weight by 4-7% and feed intake by 3-9% (Trials 1 and 2). Tibia values indicated that with low mineral P supplementations (0.05 and 0.10%), phytase additions have a non-significant effect on bone mineralization. If mineral P is not added, the tibia values show a marked response to phytase (Trial 3). Utilization of P increased from 50.9% to 60.0% when phytase (1000 PU/g) was added to the diets without mineral P supplementation (Trial 3). Utilization of P was only 34.5% in the positive control diet (0.3% mineral P). The results were obviously affected by the intrinsic phytase activity in grain and the dietary calcium level, and suggest that, in SBM-grain-based diets with very low (0.05%) or no mineral P supplementation, weight gain can be increased by adding phytase up to 1000 PU/g. This supplemented phytase activity is apparently sufficient for adequate bone mineralization.